Pemulihan ekonomi nasional pada masa pandemi Covid-19: analisis produktivitas tenaga kerja sektor pertanian - M. Zainul Abidin (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2021)
This study aims to determine the impact of the Covid-19 pandemic on labor productivity in the agricultural and the National Economic Recovery (PEN) Program to support labor productivity in the agricultural sector. This research method is descriptive qualitative using secondary data. The results showed that the Covid-19 pandemic had an impact on labor productivity in the agricultural sector. The pandemic increases health risks, disrupts agricultural production and marketing, increases the burden of health expenditures, and reduces access to education and training. The PEN program supports the productivity of the agricultural sector workforce by providing assistance and developing the capacity of the farm workforce using the distribution of social assistance (bansos) and additional pre-employment card allocations. The social assistance and capacity-building program for the agricultural workforce enabled the agricultural workforce to continue working and being productive, thus supporting the sustainable development of the farming sector.